Persepsi Mahasiswa Tahap Akademik Terhadap Pelaksanaan Progress Test di Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa - Made Ilora Hiranandasastri; Rima Kusuma Ningrum; Saktivi Harkitasari (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
[Student Perceptions of the Academic Stage on the Implementation of the Progress Test at the Faculty of Medicine and Health Sciences Warmadewa University] Medical education assesment requires a periodic comprehensive and measurement tool to assessing student competence. FKIK UNWAR holds a progress test at the end of every odd semester to evaluate competency in learning achievment. The purpose of this study to describe the perceptions of academic stage medical students towards the implementation of progress tests at FKIK UNWAR. This research is quantitative descriptive. Data used retrospective method. The population in this study were 2016, 2017, 2018 and 2019 FKIK UNWAR students. The sampling technique was total sampling. In 2020 students who have carried out the progress test will be given a self-evaluation questionnaire and an assessment of students at the academic stage of the implementation of the progress test. Data processing was performed using SPSS with univariate analysis. The results showed that the implementation of the progress test stated that 67.1% had good perceptions and 32.9% had poor perceptions. Preparation for the student progress test stated that 70.2% had a good perception and 29.8% had a bad perception. The progress test as a knowledge assessment stated that 67.4% had a good perception and 32.6% had a poor perception. It can be concluded, the results of the analysis in this study found that all respondents had a good perception of the implementation of the progress test, the preparation for the progress test, and the progress test as a knowledge assessment.